Variation in acute myocardial infarction management by kidney function across hospitals in England: a cross-sectional study using the Myocardial Ischaemia National Audit Project (MINAP) - Dorothea Nitsch; David Adlam; Clive Weston; Richard Grieve; John Deanfield; Mark De Belder; Patrick Bidulka; Rob Konstant-Hambling (BMJ Open)
Objectives We hypothesised that there is substantial variation in acute myocardial infarction (AMI) treatment across English hospitals, particularly for people hospitalised for non-ST-elevation myocardial infarction (NSTEMI) and with reduced kidney function. This study aimed to describe this variation at the hospital and the individual level to understand treatment variation and potential disparities in AMI management among people with reduced kidney function.Design Cross-sectional study.Setting Secondary care in England.Participants People hospitalised for AMI (ST-elevation myocardial infarction (STEMI) or NSTEMI) in English hospitals and captured in the Myocardial Ischaemia National Audit Project, 2014 to 2019. Kidney function was defined using estimated glomerular filtration rate (eGFR) derived from the serum creatinine recorded within 24 hours of AMI admission.Outcome measure The primary outcome was recorded invasive cardiac intervention (at least one of angiography, percutaneous coronary intervention and coronary artery bypass graft) compared with conservative management.Results We included 361 259 people with a first hospitalisation for AMI (STEMI or NSTEMI) at 209 hospitals for hospital-level analyses and 292 572 people with complete covariable data at 207 hospitals for individual-level analyses. We found substantial variation in the mean proportion of people with NSTEMI managed invasively across hospitals in England. At the individual level, using multivariable logistic regression to derive adjusted predicted probabilities to describe the association between kidney function and AMI management (invasive vs conservative management), we found that people had a lower adjusted predicted probability of being treated with invasive cardiac management with worsening eGFR range, particularly for NSTEMI cases (eGFR range 2: 76.6% (95% CI 76.3 to 76.8) vs eGFR range 5: 44.5% (95% CI 41.2 to 47.5)).Conclusions There is substantial AMI treatment variation across hospitals in England, particularly among people hospitalised for NSTEMI with reduced kidney function. Further research is needed to evaluate the comparative effectiveness of NSTEMI management strategies for complex patients.